INDICATORS OF AGGRESSIVENESS IN THE MILITARY PERSONNEL (Psychology Travelogs, 2023)
The article is devoted to the problem of aggressiveness among military personnel. The purpose of the article is to find out the general trend regarding manifestations of aggressiveness among servicemen of the Armed Forces of Ukraine. The study of military personnel was conducted at the base of one of the military units in the city of Khmelnitsky. The sample of subjects was 30 people aged from 25 to 45 years, of different sexes. The technique of diagnosing indicators and forms of aggression (Buss-Durkee Hostility Inventory, adapted by O. Osnytskyi) was used. The indicators obtained according to the scales of this technique are presented in a rounded form so that the existing trend can be seen more clearly. According to the scales «Physical aggression», «Verbal aggression» and «Annoyance», only approximately 20% of the surveyed servicemen showed a high level. According to the «Indirect aggression» and «Resentment» scales, approximately 10% of the servicemen showed a high level. About 30% of the servicemen showed a high level on the «Negativism» and «Guilt» scales. According to the «Suspiciousness» scale, 0% of the servicemen demonstrated a high level. According to the index of aggression, a high level was found in 17% of the servicemen, an average level in 50%, a low level in 33%. According to the hostility index, a high level was found in 5%, an average level in 55%, and a low level in 40%. It was concluded that despite established stereotypes about the allegedly high aggressiveness of military personnel, the studied servicemen of the Armed Forces of Ukraine showed a general tendency towards low rates of aggressive manifestations. The opinion is expressed that this trend is due to the specifics of the tasks performed by military personnel during their service and the awareness of the senselessness of excessive release of emotions and negative reactions in conditions of constant risk to life.
Keywords: military personnel; aggressiveness; physical aggression; verbal aggression; indirect aggression; autoaggression